2020
DOI: 10.1016/j.biocontrol.2020.104396
|View full text |Cite
|
Sign up to set email alerts
|

Variation in levels of acceptance, developmental success, and abortion of Halyomorpha halys eggs by native North American parasitoids

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Similarly, laboratory trials showed that native Trissolcus species are able to induce egg abortion (non-reproductive effects) in H. halys [ 25 ]. Studies carried out on North American native parasitoids suggest that there is currently no evidence of intraspecific variation in traits that allow native parasitoids to successfully develop in H. halys eggs [ 36 ]. However, the successful adaptation of native parasitoids to a new host may occur over larger timescales (i.e., decades) [ 37 ] and should be further studied in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, laboratory trials showed that native Trissolcus species are able to induce egg abortion (non-reproductive effects) in H. halys [ 25 ]. Studies carried out on North American native parasitoids suggest that there is currently no evidence of intraspecific variation in traits that allow native parasitoids to successfully develop in H. halys eggs [ 36 ]. However, the successful adaptation of native parasitoids to a new host may occur over larger timescales (i.e., decades) [ 37 ] and should be further studied in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…In the invaded areas, natural enemies have been shown to be ineffective in controlling H. halys populations as parasitism and predation rates are typically under 10% [ 19 , 20 , 21 , 22 ]. While several egg parasitoid species have been reported to readily attack H. halys egg masses, they either cannot successfully develop in this new host or exhibit highly variable parasitism levels [ 22 , 23 , 24 , 25 ]. In its native range, H. halys populations are controlled by several predatory and parasitoid species of which egg parasitoids in the genus Trissolcus play an important role [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Native natural enemies, including insect parasitoids, could potentially provide control of exotic pests in the absence of classical biological control agents. Initially, however, native parasitoids tend to be inefficient at attacking invaders due to the novelty of the exotic host (Abram et al, 2017; Chabert et al, 2012; Costi et al, 2020; Konopka et al, 2018; Kruitwagen et al, 2018). Over time, the richness and efficacy of native parasitoid complexes can increase, sometimes reaching similar levels of parasitism as on native hosts within decades or centuries (Cornell & Hawkins, 1993; Grabenweger et al, 2010; Gröbler & Lewis, 2008; Vindstad et al, 2013).…”
Section: Introductionmentioning
confidence: 99%